2018
DOI: 10.1371/journal.pone.0201315
|View full text |Cite
|
Sign up to set email alerts
|

Towards sustainable aquafeeds: Evaluating substitution of fishmeal with lipid-extracted microalgal co-product (Nannochloropsis oculata) in diets of juvenile Nile tilapia (Oreochromis niloticus)

Abstract: Microalgae companies increasingly seek markets for defatted biomass that is left over after extracting omega-3 rich oil for human nutraceuticals and crude oil for fuels. Such a protein-rich co-product is a promising alternative to unsustainably sourced fishmeal in aquaculture diets. We report the first evaluation of co-product of the marine microalga Nannochloropsis oculata (N. oculata co-product) for replacing fishmeal in diets of Nile tilapia, a globally important aquaculture species. We conducted a nutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 67 publications
2
72
3
3
Order By: Relevance
“…The high n‐3/n‐6 ratio of 2.8–3.39 obtained in the present study is due to the presence of higher proportion of DHA in the muscle tissues. This ratio is much higher than the n‐3/n‐6 ratio of 0.8–0.9 reported by Sarker et al (2018). Moreover, the high muscle n‐3/n‐6 ratios obtained in the present study compared to the recommended 1:1 ratio for optimal human health are a good indication of the nutritional and health status of tilapia raised in BFT.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The high n‐3/n‐6 ratio of 2.8–3.39 obtained in the present study is due to the presence of higher proportion of DHA in the muscle tissues. This ratio is much higher than the n‐3/n‐6 ratio of 0.8–0.9 reported by Sarker et al (2018). Moreover, the high muscle n‐3/n‐6 ratios obtained in the present study compared to the recommended 1:1 ratio for optimal human health are a good indication of the nutritional and health status of tilapia raised in BFT.…”
Section: Discussioncontrasting
confidence: 61%
“…(2014) for GIFT Nile tilapia fed diets containing different levels of perilla oils, but lower than the 5.4%–6.10% reported by Sarker et al (2018). However, the ∑SFA range of 49.59%–55.21% obtained in this study is higher than the 36.35%–36.7% found by Sarker et al (2018) in Nile tilapia fed diets containing a coproduct of marine algae ( Nannochloropsis oculata ). However, Sarker et al (2018) reported slightly higher ∑MUFA and ∑PUFA values in tilapia muscle than this study.…”
Section: Discussionmentioning
confidence: 60%
“…Already, studies have shown that cetoleic acid, which is especially high in lantern fish species, stimulates the capacity of human and salmon cells to produce EPA and DHA, and enhance the retention of EPA and DHA in Atlantic salmon [72]. One key challenge for sustainable aquaculture development is sufficient feed ingredients that can produce healthy and robust fish [17,78,79]. Currently, Norwegian farmed salmon are fed more than 70% plant feed ingredients on average [80], with similar levels in Chile, Canada and Australia, while Scotland salmon diets contain slightly higher levels of marine feed ingredients [81].…”
Section: Discussionmentioning
confidence: 99%
“…77 The nutritional quality of microalgae is high, with a crude protein content of up to 71% and a lipid content of up to 40%, which are comparable with that of terrestrial plant and animal sources. [78][79][80] Microalgae have the potential to replace fish meal and fish oil in aquafeeds 71,77,81 and many studies have demonstrated the successful use of microalgal biomass as a feed additive or fish meal replacement for a range of aquaculture species, generally with positive effects on growth and quality 70,[81][82][83][84][85][86][87] ( Figure 3C). The biological capacity of microalgae, underpinned with positive research findings on the replacement efficacy in aquafeeds across many aquaculture species, suggests that there is high potential for the use of microalgae as a protein source.…”
Section: Microbial Biomassmentioning
confidence: 99%